Fundamental justice: section 7 of the Canadian Charter of Rights and Freedoms - Stewart, Hamish (Irwin Law, 2019)
Section 7 of the Canadian Charter of Rights and Freedoms provides that "[e]veryone has the right to life, liberty and security of the person and the right not to be deprived thereof except in accordance with the principles of fundamental justice." This book analyzes all aspects of section 7. It outlines the place of section 7 in the constitutional order; how courts decide whether a particular legal principle is so fundamental that it merits recognition under section 7; the conditions under which section 7 will apply to a legal dispute; the legal norms that have been recognized, or rejected, as principles of fundamental justice under section 7; and the very limited circumstances in which an infringement of section 7 will be justified under section 1. The second edition has been extensively revised to take into account several significant changes in the law over the last several years, including the Supreme Court of Canada's decisions in Bedford (sex work) and Carter (medically assisted dying).